An Ethical Decision-Making Framework for Competitor Intelligence Gathering - Rittenburg, Terri L. (Journal of business ethics, 2007)
Competitor intelligence gathering involves the aggregation of competitive information to facilitate strategic development and a competitive advantage. Unfortunately, companies are sometimes willing to carry out questionable gathering practices to collect such information. An ethical decision making framework for competitor intelligence gathering is presented in this paper that outlines the impact of several strengthening and weakening factors on individual ethical reasoning. Dialogue is provided about the management of intelligence gathering from various viewpoints, and the implications of these managerial suggestions are discussed.